1993
DOI: 10.1063/1.464946
|View full text |Cite
|
Sign up to set email alerts
|

Icosahedral, decahedral, fcc, and defect-fcc structural models for ArN clusters, N≳500: How plausible are they?

Abstract: Different structural models for solid argon clusters with more than 500 atoms, that have been proposed previously on the basis of energy considerations, but whose origin and growth histories are not well understood, are compared with other models that have been devised mainly to overcome these difficulties, at the expense, however, of a smaller binding energy. Diffraction functions have been calculated for a variety of structures and sizes, and are compared with the observed electron-diffraction patterns obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 93 publications
3
43
0
Order By: Relevance
“…1 In spite of the huge improvements in spectroscopic techniques during the last few decades, fundamental characteristics still remain unclear: no accordance has been found on the cluster size above which the lattice structure changes from fcc to hcp. 2,3 Moreover, small clusters have been assigned to liquid-like behavior [4][5][6] and the cluster size above which these clusters solidify is not yet well-characterized. The study of the above mentioned characteristics is limited by the transparency of rare gas clusters in the visible range, limiting the use of many standard spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%
“…1 In spite of the huge improvements in spectroscopic techniques during the last few decades, fundamental characteristics still remain unclear: no accordance has been found on the cluster size above which the lattice structure changes from fcc to hcp. 2,3 Moreover, small clusters have been assigned to liquid-like behavior [4][5][6] and the cluster size above which these clusters solidify is not yet well-characterized. The study of the above mentioned characteristics is limited by the transparency of rare gas clusters in the visible range, limiting the use of many standard spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous theoretical work [43] and electron diffraction experiments [44] a critical size for a structural change from icosahedron to fcc in Ar clusters is at least 750 atoms. However, recently Kakar et al [45] observed fcc-sensitive maxima in EXAFS measurements on Ar clusters already at 〈N〉 ~ 200.…”
Section: Resultsmentioning
confidence: 99%
“…The icosahedral structure does not belong to the fcc basis and according to theoretical studies of the total binding energy, this structure is favored until a certain size (number of atoms) is reached (see e.g. [43]). On the other hand, a structural change towards fcc must take place at some size, since an infinite lattice cannot be built from an icosahedral symmetry, and the fcc structure is also energetically favored for very large cluster sizes, where surface strain does not play a role.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this is a structural transition from planar geometries to 3D ones, which occurs between N = 5 and N = 7 on the Bolding-Andersen surface. Such a drastic change is a peculiarity of the small cluster range studied here; there are also structural transitions in the higher-N range [21], but they are less severe.…”
Section: Exemplary Applicationmentioning
confidence: 96%